Multiple lesions by vampire bat bites in a patient in Niterói, Brazil - Case report - Fred Bernardes Filho; Gustavo Martins; Gustavo Sabaini Luchi; Bernard Kawa Kac; José Augusto da Costa Nery; Luna Azulay-Abulafia; David Rubem Azulay (Sociedade Brasileira de Dermatologia, 2014)
Over the last few centuries, the expansion of urbanization brought bats closer to urbanized areas, increasing the risk of accidents by bat bites. The morphology of bat bites can be varied, usually having an elliptical shape, about 0.5 cm along its greatest length, and the characteristic corkscrew bite pattern. The authors present the case of a patient who was repeatedly bitten by vampire bats for two months. A polymerase chain reaction was performed in the cutaneous nerves at the base of the hair follicles which showed negativity towards the rabies virus. The authors highlight the public health importance of this case, and discuss the morphological characteristics of these hematophagous bat bites.